The Semantic Roles Which Cause Difficulty To The Fourth Year Students Of English At The University Of Anbar - Shwaysh Ahmed, Muslih; Hayif Sameer, Imad; Yassein Al-Heeti, Mohammed Talib (Opción, 2019)
The present study aims at investigating the difficulty of identifying the cases of Semantic Roles that encounter the fourth year students of English at the University of Anbar. Also, it aims at identifying which group (i.e. students who study English at College of Arts or those who study English at College of Ed- ucation for Humanities) faces more difficulty in the Semantic Roles than the other, and the third aim is to find out if there is a significant difference in the Semantic Roles difficulty between males and females of the whole sample ac- cording to the variable of gender. This study is restricted to investigate if the fourth year students of English at the University of Anbar encounter difficulty in deciding the cases of Semantic Roles adopted by Fillmore during the second course of the study year 2017-2018. The present study hypothesizes that there is no significant difference between the mean score of the sample’s achieve- ment in the test, on one hand and the estimated theoretical mean of the test on the other hand at level of significance (0.05). The second hypothesis states that there is no significant difference in Semantic Roles difficulty between the group of the fourth year English language students at the College of Arts and the fourth year English language students at College of Education for Human- ities at the level of significance (0.05), and the final hypothesis is that there is no significant difference in the Semantic Roles difficulty between males and females of the whole sample according to the variable of gender and at the level of significance (0.05). The researchers have chosen the sample randomly. It includes (61) students distributed to 28 male and female students who study English in the fourth year at College of Arts and 33 male and female stu- dents who study English in the fourth year at College of Education for Hu- manities. The researchers used a diagnostic test as the main instrument to collect the required data. After applying the test, one sample t-t test is used to accomplish the first aim and two independent samples t-test is used to achieve the second and third aims of this study. Results show that the sam- ple of the study totally faces problems in determining the cases of semantic roles adopted by Fillmore. With respect to the second aim, it is found that the group of College of Arts and College of Education for Humanities suffer from a similar difficulty in identifying the cases of semantic roles. Also, it is found that females’ achievements in the test in both groups are better than males’ achievements in both groups. Finally conclusions, suggestions and recommendations are set.